WAKTU MEMBACA ĀMĪN BAGI MAKMUM DALAM SHALAT ‎JAHRIYAH: ‎STUDI TEMATIK HADIS-HADIS SHAHIH - Abbad, Abdurrahman; Muhammad Ilyas (CBJIS: Cross-Border Journal of Islamic Studies, 2025)
This research investigates the proper timing for the congregation to recite Āmīn in ‎audible ‎‎(jahrīyah) prayers, addressing variations in practice among Muslim ‎communities. Employing ‎a qualitative descriptive method with a thematic (mawḍūʿī) ‎ḥadīth approach, it examines ‎narrations from Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, and ‎other canonical sources, supported by ‎classical and contemporary juristic discussions. ‎The findings highlight that authentic ḥadīths, ‎particularly the well-agreed narration of ‎Abū Hurayrah, indicate that the congregation should ‎recite Āmīn simultaneously with ‎the imam. Juristic opinions diverge: the Shāfiʿī and Ḥanbalī ‎schools emphasize ‎simultaneity, while the Mālikī and Ḥanafī schools favor recitation after ‎the imam. ‎Through tarjīḥ analysis, the Shāfiʿī and Ḥanbalī view is deemed stronger as it aligns ‎‎with the textual evidence and promotes collective harmony. The study concludes that ‎‎reciting Āmīn embodies both spiritual value—as a supplication for divine mercy—and ‎social ‎value as a symbol of unity in congregational worship.‎